2017
DOI: 10.18512/1980-6477/rbms.v16n3p460-468
|View full text |Cite
|
Sign up to set email alerts
|

Respostas Morfoagronômicas De Milho Submetido a Desfolha Artificial

Abstract: RESUMO -O objetivo deste estudo foi avaliar as características morfoagronômicas do híbrido simples de milho em função da aplicação de diferentes intensidades de desfolha artificial, realizadas no estádio R1 de desenvolvimento. O experimento foi conduzido na área experimental do Instituto Federal Goiano,em Morrinhos-GO, na safra 2015/2016.Foi aplicado o delineamento de blocos completamente casualizados, com oito tratamentos e quatro repetições, sendo eles: remoção de uma folha acima e uma abaixo da espiga; remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Regarding prolificity, no significant difference was observed between treatments (Tables 2 and 3), corroborating Alvim et al (2010) and Trogello et al (2017) who found that prolificity is negatively affected only when a complete leaf removal is performed. Tinca et al (2015) pointed out that prolificity is intrinsically related to genotypic factors previously determined in their genetic improvement, however, adequate management and edaphoclimatic conditions may indirectly interfere with this trait.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Regarding prolificity, no significant difference was observed between treatments (Tables 2 and 3), corroborating Alvim et al (2010) and Trogello et al (2017) who found that prolificity is negatively affected only when a complete leaf removal is performed. Tinca et al (2015) pointed out that prolificity is intrinsically related to genotypic factors previously determined in their genetic improvement, however, adequate management and edaphoclimatic conditions may indirectly interfere with this trait.…”
Section: Resultssupporting
confidence: 80%
“…Consequently, this behavior reflected directly on the weight grain per ear and ears weight (Table 5). So, a critical period (R1 to R3) was observed in corn crop in relation to loss of leaf area and its effects on plant reproductive characteristics, which was also evidenced by Trogello et al (2017), when they observed that in stage R1, as defoliation intensity increased, there was a reduction in the weight of one thousand grains, grain weight per ear and ear weight. Additionally, Alvim et al (2010) reported that the weight of one thousand grains is intrinsically related to the source and drainage capacity of the plant, where defoliation from R3 no longer influences this characteristic, since the grains have their photoassimilates guaranteed for their complete formation and filling.…”
Section: Resultsmentioning
confidence: 88%